Esketamine combined with ultrasound-guided superficial cervical plexus block to complete pediatric subglottic stenosis tracheotomy-a case report and literature review - Guangyan Zhang; Baoping Wang; Haifeng Li (BMC Anesthesiology)
Abstract Background Congenital subglottic stenosis is a condition that results in airway narrowing in pediatric patients, presenting significant challenges for anesthesiologists during surgical procedures. This case report describes the successful management of a pediatric patient with congenital subglottic stenosis who underwent tracheotomy using esketamine combined with ultrasound-guided superficial cervical plexus block. The aim is to provide an alternative anesthetic approach for similar complex cases. Case presentation A 4-year-old child diagnosed with congenital subglottic stenosis and laryngeal obstruction (grade III) required emergency tracheotomy to alleviate the obstruction. Esketamine was selected as the sedative-analgesic agent to maintain spontaneous breathing. Ultrasound-guided bilateral superficial cervical plexus blocks were performed to enhance analgesia. The tracheotomy was successfully completed without any intraoperative movement or coughing. Postoperatively, the patient recovered well and was discharged from the hospital. Conclusion The combination of esketamine and ultrasound-guided superficial cervical plexus block offers a safe and effective anesthetic approach for this pediatric patient with subglottic stenosis undergoing tracheotomy. Further studies are necessary to confirm the safety and efficacy of this technique.